Challenge of Liquid Stressed Protective Materials and Environmental Persistence of Ebola Virus - Nikiforuk, Aidan M. (Sci Rep, 2017)
After the largest Ebola virus outbreak in history, experts have attempted to answer how the Zaire ebolavirus species emerged in West Africa and caused chains of human-to-human transmission. The widespread and untimely infection of Health Care Workers (HCW) in the affected countries accelerated spread of the virus within the community. Among the reasons attributed to this trend, it must be considered that HCW were exposed to the virus in their occupational environment. The contribution of environmental conditions to the spread of Ebola in West Africa was examined by investigating the effect of temperature/humidity on the virus’s environmental persistence and by modeling if saturation (liquid stress) allows for penetration of Ebola virus through personal protective equipment (PPE). Ebola-Makona virus persisted on PPE and materials found in outbreak settings for less than 72 hours at 27 °C and 80% relative humidity (RH). A difference in virus penetration was observed between dry (5%, 1/21 tests) and saturated (33%, 7/21 tests) samples of PPE. Infectious virus particles penetrated through saturated coupons of Tyvek Micro Clean, Tychem QC, whole surgical masks and N95 respirators. These findings suggest inclusion of saturation or similar liquid stress simulation in protective equipment testing standards.